THE IMPACT OF GRAINS TRANSPORTATION REVENUES ON TOTAL REVENUE: THE CASE OF SERBIA - Kontić, Ljiljana; Vukasović, Dragan (Economics of Agriculture, 2017)
In this paper the values effects of grain transportation on total revenue have been analyzed. The subject of the study is one Serbian cargo company. Main aim of this research was to assess the impact of revenue from grain transportation on total revenue in order to extrapolated future trends in cargo sector. The starting hypothesis was that aforementioned revenue had signifcant influence on total revenue growth in observed period. Mixed methods research has been used for data collection and analysis. The results revealed that the movement of the total revenue growth in the coming years if they implement the necessary measures are in the extrapolation of this function presented, provided that all other variables remain unchanged. Limitation of the study were countrys specifc factors, and single case study analysis despise the fact that observed company had dominant market share. Future study will include other companies from similar transition countries.